Support for Family Relationships with Adherence to Taking Medication and the Risk of Recurrence in Patients Experiencing Hallucinations at Work Area Health Centers - Rio Wiranda Saputra; Edi Sukamto; Badar (Indonesian Journal of Sport Management and Physical Education, 2023)
Hallucinations are a symptom of sensory perceptual disturbances experienced by patients with mental disorders. The cause of relapse is not taking medication and to increase adherence to taking medication it is necessary to have family support. This study aims to determine the relationship between family support and medication adherence and the risk of recurrence in hallucinatory patients. This type of research uses a quantitative type with a correlation method through a cross sectional approach.Data collection was carried out using a questionnaire using the Spearman rank statistical test. The results showed that 50 respondents (100%) had good family support, 46 respondents (92%) had high adherence, and 46 respondents (92%) had no relapse risk. Based on the results of research on the relationship between family support and adherence to taking medication with a p= 0,000 it can be concluded that there is a relationship between family support and adherence to taking medication in hallucinatory patients. Based on the results of research on the relationship between family support and the risk of recurrence with a p= 0,002 it can be concluded that there is a relationship between family support and the risk of recurrence of hallucinatory patients